JUDICIAL REVIEW OF DISMISSION AND LIQUIDATION PROCESS FOR LIMITED LIABILITY COMPANY POST BANCRUPTCY - Bing Yusuf (UNTAG Law Review, 2017)
Starting from registration and licensing of the establishment until the end which is dismission and liquidation. From the beginning until the end of the existence of a Limited Liability Company, consists of many operational activities related to the business as regulated in Statute of Law Number 40 of year 2007 which legislate Limited Liability Company. At the end of the life cycle of the Limited Liability Company, there are three stages, they are dismission, liquidation, and ultimately revocation of the legal entity status of a Limited Liability Company. The main principle of this stage is as stated in a proverb on justice derived from Latin means that the basic principle of the law is to live a respectable life, not harming others, and to give others what is their due, so ideally the rule of law is implemented. In fact there is a dispute in the implementation of the stages of dismission, liquidation and revocation of legal entity status due to injustice and fraudulent acts committed by individuals, Therefore this research will be discussing the aspects that trigger the dispute, to the analysis on litigation process, and ultimately the researcher provides a solution to avoid the same disputes occur in accordance with the regulations of the Statute. This research was studied using descriptive analysis with normative juridical approach, supported by primary and secondary data source from literature study. It was found that the occurrence of a dispute was caused by an irresponsible director. Not responsible in carrying out his duties to do the General Meeting of Shareholders and submit the remaining treasury from bankruptcy process. Proceeded to the litigation process where the court declared that the court was not authorized according to relative competence in giving the decree of dismission. However, at the level of cassation, the decree was canceled. Problems as such should not occur in the first place if the director has been professional and responsible due to his duty.